High Crystalline Prussian White Nanocubes as a Promising Cathode for Sodium‐ion Batteries. Issue 3 (17th January 2018) - Li, Cong; Zang, Rui; Li, Pengxin; Man, Zengming; Wang, Shijian; Li, Xuemei; Wu, Yuhan; Liu, Shuaishuai; Wang, Guoxiu
Abstract: Prussian blue and its analogues (PBAs) have been recognized as one of the most promising cathode materials for room‐temperature sodium‐ion batteries (SIBs). Herein, we report high crystalline and Na‐rich Prussian white Na2 CoFe(CN)6 nanocubes synthesized by an optimized and facile co‐precipitation method. The influence of crystallinity and sodium content on the electrochemical properties was systematically investigated. The optimized Na2 CoFe(CN)6 nanocubes exhibited an initial capacity of 151 mA h g −1, which is close to its theoretical capacity (170 mA h g −1 ). Meanwhile, the Na2 CoFe(CN)6 cathode demonstrated an outstanding long‐term cycle performance, retaining 78 % of its initial capacity after 500 cycles. Furthermore, the Na2 CoFe(CN)6 Prussian white nanocubes also achieved a superior rate capability (115 mA h g −1 at 400 mA g −1, 92 mA h g −1 at 800 mA g −1 ). The enhanced performances could be attributed to the robust crystal structure and rapid transport of Na ions through large channels in the open‐framework. Most noteworthy, the as‐prepared Na2 CoFe(CN)6 nanocubes are not only low‐cost in raw materials but also contain a rich sodium content (1.87 Na ions per lattice unit cell), which will be favorable for full cell fabrication and large‐scale electric storage applications. Abstract : Inside the White (Nano)Cube : High crystalline and Na‐rich Prussian white nanocubes were prepared using an optimized and facile co‐precipitation method. The influence of crystallinity and sodium content on the electrochemical performances of the materials was investigated. The as‐prepared Na2 CoFe(CN)6 nanocubes presented outstanding electrochemical performances.